Directed tunneling of a prescribed number of dipolar bosons in shaken triple-well potentials. (24th July 2015) - Luo, Xiaobing; Wang, Yueming; Yu, Xiaoguang; Guo, Yu; Chong, Guishu; Wu, Donglan; Hu, Qianglin
Abstract: We propose a scheme for precise control of the tunneling dynamics of dipolar bosons in shaken triple-well potentials. In high-frequency regimes and under resonance conditions, we have analytically and numerically demonstrated that we can transport an a priori prescribed number of dipolar bosons along different pathways and in different directions by adjusting the driving parameters. These results extend the previous many-body selective coherent destruction of tunneling schemes for nondipolar bosons in double-well potentials (Gong et al 2009 Phys. Rev. Lett. 103 133002 ; Longhi 2012 Phys. Rev. A86 044102 ), thus offering an efficient way to design long-range coherent quantum transportation.